< Chan Chan > y su trampa etimológica: respuesta a Cerrón-Palomino - Urban, Matthias (Pontificia Universidad Católica del Perú, 2022)
This contribution concerns once again the name of Chan Chan, the largest pre-Hispanic city in the Americas. Rodolfo Cerrón-Palomino has recently argued that the name should be etymologized through a combination of Quechua, which had a weak and short-lived presence on the Peruvian North Coast, and Aymara material, a language which had no known presence there at all. In addition to this major flaw, I discuss further problematic aspects of the proposal. Each of these would suffice to cast considerable doubt on the proposed etymology, but in conjunction they make it advisable to reject it outright. Instead, I continue to defend a methodologically conservative and cautious posture that I have already advocated in my earlier contribution to the topic

La presente contribución concierne de nuevo el nombre de Chan Chan, la ciudad prehispánica más grande en toda América. Recientemente, Rodolfo Cerrón-Palomino sostuvo que el nombre debe ser etimologizado a través de una combinación de material quechua, que tuvo una presencia tenue y efímera en la costa norte peruana, y aimara, una lengua que no cuenta con ninguna presencia conocida allá en absoluto. Además de esta falla básica, discuto otros aspectos problemáticos de la propuesta. Cada uno de estos bastaría para poner en duda la etimología propuesta, pero en conjunto aconsejan rechazarla rotundamente. En su lugar, sigo defendiendo una postura metodológicamente conservativa y cautelosa que ya había propugnado en mi anterior contribución a la temática.
< Chan Chan > and its etymological trap: response to Cerrón-Palomino
Keywords: Chan Chan; Etymology; toponymy; North Coast of Peru; Chan Chan; Etimología; Toponimia; Costa norte peruana; https://purl.org/pe-repo/ocde/ford#6.02.06